PRINCE MUHAMMAD BIN SALMAN'S REFORM POLICY FOR WOMEN'S RIGHTS FREEDOM IN SAUDI ARABIA 2017-2022 - Ginting, Cindy Arista; Raharjo, Ratnawati (Jurnal Paradigma, 2025)
The freedom of Saudi women is inseparable from the role of Prince Muhammad Bin Salman as the crown prince of the kingdom of Saudi Arabia, the freedom of Saudi women is one form of manifestation of social reform that has been planned since the reign of King Abdullah which was then realized during the leadership of King Salman bin Abdulaziz Al Saud through the Arab Vision 2030 initiated by Prince Muhammad Bin Salman. Arab Vision 2030 has succeeded in realizing the demands of Saudi women regarding gender equality, where this equality has been seen with the existence of women who have been allowed to drive and have a personal driver's license without having to ask permission from their guardians. In addition, Saudi women have also been allowed to participate and be involved in politics, are also allowed to choose jobs and build their own businesses and women are also allowed to obtain education up to college with freedom in choosing majors. In this study, the author uses conceptual theories, namely political system theory and legitimacy needs, where this theory will explain the objectives of the study. For the method used, namely the explanatory method with a qualitative research type.